Polyvinyl alcohol nanofibers reinforced with polybenzimidazole: Facile preparation and properties of an anion exchange membrane. (2nd May 2021) - Coppola, Roxana E.; Molinari, Fabricio N.; D'Accorso, Norma B.; Abuin, Graciela C.
Abstract: The search of novel materials for anion exchange membranes (AEMs) is a key factor in addressing challenges of electrochemical energy conversion and storage devices in terms of cost, durability, efficiency, and up‐scalability; and composite materials based in electrospun nanofibers have a great potential in this regard. We report a facile preparation method of an AEM composed by polyvinyl alcohol (PVA) nanofibers crosslinked with glutaraldehyde (GA) and reinforced with poly[2‐2′‐(m‐phenylene)‐5‐5′‐bibenzimidazole] (ABPBI) polymer, characterizing it as an AEM in a liquid alkaline water electrolyzer (LAWE) device. Homogeneous and flexible membranes were obtained, with a good chemical stability in the doping solution (15 wt.% KOH), and better swelling resistance than pure ABPBI membranes. The membranes also showed a specific ionic conductivity of 36 mS·cm −1 at 60°C and 41 mS·cm −1 at 80°C, with an activation energy value of 3.5 kJ·mol −1 . Regarding LAWE performances, it attained current densities of 236 and 271 mA·cm −2 for a 2 V cell voltage when operated at 50°C and 70°C, respectively. During chronopotentiometric test, neither potential drop nor change in material integrity were observed. These results provide a facile and scalable method for low cost AEMs preparation, contributing as an alternative material for its use in electrolyzers.